2006
DOI: 10.1190/1.2212276
|View full text |Cite
|
Sign up to set email alerts
|

AVA simultaneous inversion of partially stacked seismic amplitude data for the spatial delineation of lithology and fluid units of deepwater hydrocarbon reservoirs in the central Gulf of Mexico

Abstract: This paper describes the successful application of amplitude-versus-angle (AVA) inversion of prestack-seismic amplitude data to detect and delineate deepwater hydrocarbon reservoirs in the central Gulf of Mexico. Detailed AVA fluid/lithology sensitivity analysis was conducted to assess the nature of AVA effects in the study area based on well-log data. Standard techniques such as crossplot analysis, Biot-Gassmann fluid substitution, AVA reflectivity modeling, and numerical simulation of synthetic gathers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…We recall that the l 1 -norm minimization method (sometimes it is referred as sparsespiky regularization in geophysics community) is quite important for seismic inversion (Claerbout and Muir 1973;Contreras et al 2006). This is because that the l 1 -norm could penalize outliers and large amplitude anomalies.…”
Section: Comparison With the Linear Programming Methodsmentioning
confidence: 99%
“…We recall that the l 1 -norm minimization method (sometimes it is referred as sparsespiky regularization in geophysics community) is quite important for seismic inversion (Claerbout and Muir 1973;Contreras et al 2006). This is because that the l 1 -norm could penalize outliers and large amplitude anomalies.…”
Section: Comparison With the Linear Programming Methodsmentioning
confidence: 99%
“…A numerical rock model is built to predict the elastic properties of the rock from the petrophysical properties [Sams 2007]. AVA deterministic simultaneous inversion is based on amplitude-versus-angle-constrained sparse spike inversion algorithm [Contreras 2006] which is an extension of the original constrained sparse spike inversion algorithm [Debeye 1990]. The inversion is a global, traced-based process that converts amplitudes from multiple partial angle stacks into P-impedance, Vp/Vs and Density volumes (elastic properties) which have higher resolution than the input seismic data.…”
Section: Methodsmentioning
confidence: 99%
“…This technique which has been extended and widely publicised by Hedlin 2000, Hilterman 2001, Russell et al, 2003, and Contreras et al, 2006 has found wide application in industry, and has been employed in several successful theoretical and field studies in Niger Delta basin (see, for example Omudu et al, 2006Omudu et al, , 2008. Figure 2 shows crossplots of Ip versus Is and λρ versus µρ, colour coded with resistivity.…”
Section: Introductionmentioning
confidence: 96%